25.6k views
2 votes
3/2 (4x-1) -3x = 5/4 -(x+2)

2 Answers

2 votes

Answer:

3/16

Explanation:

32(4x−1)−3x=54−(x+2)

32(4x−1)−3x=54+−1(x+2)(Distribute the Negative Sign)

32(4x−1)−3x=54+−1x+(−1)(2)

32(4x−1)−3x=54+−x+−2

(32)(4x)+(32)(−1)+−3x=54+−x+−2(Distribute)

6x+−32+−3x=54+−x+−2

(6x+−3x)+(−32)=(−x)+(54+−2)(Combine Like Terms)

3x+−32=−x+−34

3x+−32=−x+−34

Step 2: Add x to both sides.

3x+−32+x=−x+−34+x

4x+−32=−34

Step 3: Add 3/2 to both sides.

4x+−32+32=−34+32

4x=34

Step 4: Divide both sides by 4.

4x4=344

User Pajar Fathurrahman
by
5.9k points
5 votes

Answer:

x=3/16

Explanation:

User StefanOS
by
6.2k points